Measuring S100 protein and neurone specific enolase in melanocytic tumours using video image analysis. Issue 10 (October 1986) - Williams, R A; Rode, J; Dhillon, A P; Jarvis, L R; Skinner, J M; Jamal, O
Abstract : Using a computed video image analysis system, the staining intensity for both neurone specific enolase (NSE) and S100 protein was measured in sections from 19 malignant melanomas and 16 benign melanocytic lesions. The results of this study confirm previous reports that NSE and S100 protein are useful markers for malignant melanoma. NSE staining intensity in the cases of malignant melanoma was significantly higher than that in benign naevi (p = 0.011). Intensity of staining for S100 protein was not significantly higher in the malignant melanomas. There was, however, a significant S100 gradient when comparing superficial and deep intradermal portions of these tumours (p = 0.003). This feature was not seen in benign naevi. The greatest intensity of S100 protein staining was found in the deeper portions of the malignant melanomas. This gradient difference was not seen with staining for NSE. Although it seems that the overall intensity of staining for NSE is more effective in differentiating between benign and malignant lesions, the difference in staining intensity between the superficial and deep portions of the tumour may be the better indicator of adverse behaviour in lesions in which the diagnosis of malignancy is uncertain.